Self-rated health changes of individuals in same-sex compared to different-sex relationships: a longitudinal study - Yiwen Wang (BMC, 2022)
Abstract Background Prior scholarship on same-sex relationships and health has primarily relied on cross-sectional data, leaving a number of unanswered questions about health changes of same-sex couples over time. This study examined the self-rated health statuses and changes of individuals in same- and different-sex cohabitations and marriages over time (2014-2017). Methods Data were drawn from the 2014 panel of the Survey of Income and Program Participation (SIPP), a nationally representative and longitudinal study (N = 23,297) in the United States. Mixed- and fixed-effects regression models were performed to investigate the self-rated health changes of individuals in same-sex compared to different-sex relationships. Results Results show that same-sex married individuals report a faster decline in self-rated health compared to different-sex married counterparts despite similar initial health statuses. Similarly, same-sex cohabitors also exhibit a more rapid health decline as compared to different-sex cohabitors. Conclusions The results point to health change disadvantages experienced by same-sex married and cohabiting individuals during the study period. The findings from this study advance scholarly knowledge on the health changes of individuals in marginalized intimate relationships and highlight the importance of studying sexual minorities' health using longitudinal data.